2021
DOI: 10.3389/fgene.2021.682707
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and Evaluating Fetuses With Ventriculomegaly in Genetic Etiologic Studies

Abstract: The association between genetics and fetuses with ventriculomegaly (VM) is unknown. This study aimed to classify and evaluate abnormal copy number variations (CNVs) in fetuses with VM. From December 2016 to September 2020, amniotic fluid or umbilical cord blood from 293 pregnant women carrying fetuses with VM was extracted for single-nucleotide polymorphism microarray (SNP array). Among 293 fetuses with VM, 31 were detected with abnormal CNVs, including 22 with pathogenic CNVs (7.51%) and nine with variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
3
1
Order By: Relevance
“…With the development of molecular genetic technology, CMA has been gradually applied to detect these chromosomal submicroscopic imbalances due to higher resolution. For our VM cases, the detection rate of chromosomal abnormality using CMA was 16.5%, slightly lower than some studies reporting 17.9–20.6% ( 2 , 17 ) and higher than other studies reporting 6.2–16.3% ( 3 , 10 , 11 , 18 – 20 ). It has been reported that CMA could yield an additional detection rate as a first-tier diagnostic tool in VM, with an incremental yield ranging from 5 to 26% ( 1 , 8 ).…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…With the development of molecular genetic technology, CMA has been gradually applied to detect these chromosomal submicroscopic imbalances due to higher resolution. For our VM cases, the detection rate of chromosomal abnormality using CMA was 16.5%, slightly lower than some studies reporting 17.9–20.6% ( 2 , 17 ) and higher than other studies reporting 6.2–16.3% ( 3 , 10 , 11 , 18 – 20 ). It has been reported that CMA could yield an additional detection rate as a first-tier diagnostic tool in VM, with an incremental yield ranging from 5 to 26% ( 1 , 8 ).…”
Section: Discussioncontrasting
confidence: 79%
“…Chang et al ( 2 ) reported a 12.1% rate of chromosomal abnormalities in 281 fetuses with VM ( 2 ). Among the abnormal karyotypes in fetuses with VM, trisomy 21 was found to be the most common chromosomal aneuploidy ( 2 , 3 , 10 , 11 ), which was also observed in our VM cases. As known, chromosomal CNVs smaller than 5 Mb could hardly be identified by karyotyping.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations